Peroral endoscopic myotomy versus pneumatic dilation – result from a retrospective study with 1-year follow-up - Zheng, Zhongqing; Zhao, Chunshan; Su, Shuai; Fan, Xiaofei; Zhao, Wei; Wang, Bin; Jin, Hong; Zhang, Lili; Wang, Tao; Wang, Bangmao (Zeitschrift für Gastroenterologie, 2019)
Background and aims On the basis of lesser rates of major adverse events and a short-term efficacy as Heller’s myotomy, there is a growing enthusiasm in favor of peroral endoscopic myotomy (POEM), whereas study comparing POEM and pneumatic dilatation (PD) is quite rare. The aim of this study was to evaluate the efficacy of POEM and PD in Chinese achalasia patients in a retrospectively designed study.Methods Patients with achalasia, who underwent either PD (n = 26) or POEM (n = 40) were retrospectively recruited from September 2010 through March 2016 at a single tertiary center. During the 1-year follow-up, clinical outcome and functional data of lower esophageal sphincter (LES) were recruited. Clinical symptoms were assessed by use of the Eckardt score. The primary outcome was therapeutic success (Eckardt score ≤ 3). Functional data of LES (4-second integrated relaxation pressure [4s-IRP], LES relax rate, and LESP) at baseline and 1 month after treatment were also evaluated. Data was analyzed by SPSS 13.0 version using a significance level of p < 0.05.Results The success rates were 24/26 (92.31 %), 25/26 (96.15 %), and 24/26 (92.31 %), respectively, with POEM, as compared with 35/40 (87.50 %), 29/40 (72.50 %), and 23/40 (57.50 %), respectively, with PD, 1 month, 3 months, and 1 year after treatment. Statistically significant difference was observed between the 2 therapies (at 3 months, Fisher’s exact test, p = 0.01; at 1 year, Fisher’s exact test, p < 0.0001). Compared with PD, the Eckardt score was lower with POEM 1 month, 3 months, and 1 year after treatment. More patients in POEM group reported gastroesophageal reflux symptoms (after 3 months 7/26 (26.92 %) vs. 2/40 (5.00 %), Fisher’s exact test, p = 0.01; after 1 year 6/26 (19.23 %) vs. 1/35 (2.86 %), Fisher’s exact test, p = 0.02). The postoperative 4s-IRP and LESP were both lower with POEM than with PD, respectively. Type I achalasia had a better response with POEM than with PD.Conclusion In this retrospective analysis with 1-year follow-up, POEM presents with a higher success rate and more reflux symptoms compared with PD. Change on LES function after treatment may explain the outcome in part. Type I achalasia may respond better to therapies compared with type II.
Keywords: achalasia; lower esophageal sphincter; high-resolution manometry; peroral endoscopic myotomy; pneumatic dilation